1999
DOI: 10.2118/99-13-52
|View full text |Cite
|
Sign up to set email alerts
|

Regression to Experimental PVT Data

Abstract: A procedure is presented for regression of equation of state parameters to experimental PVT-data. The starting point is a predictive C7+ characterization based on the available analytical data. If the agreement between the experimental and calculated PVT data is unsatisfactory, the first step is to critically evaluate the analytical data. If this still does not lead to satisfactory results, an adjustment of the equation of state volume translation parameter is performed. This parameter is chosen because it inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Although there is no well-defined regression scheme for step 4 due to its high flexibility in the conventional method, Figure S1 in the Supporting Information depicts the conventional regression scheme used in this research, which is based on Pedersen and Christensen 15 and Christensen. 42 Adjustments are made for T C , P C , and ω of pseudocomponents to match the P SAT at the reservoir temperature. Adjustment parameters are selected based on their sensitivities to P SAT calculation (Voulgaris et al 43 ).…”
Section: Conventional Characterization Methods Used In This Researchmentioning
confidence: 99%
“…Although there is no well-defined regression scheme for step 4 due to its high flexibility in the conventional method, Figure S1 in the Supporting Information depicts the conventional regression scheme used in this research, which is based on Pedersen and Christensen 15 and Christensen. 42 Adjustments are made for T C , P C , and ω of pseudocomponents to match the P SAT at the reservoir temperature. Adjustment parameters are selected based on their sensitivities to P SAT calculation (Voulgaris et al 43 ).…”
Section: Conventional Characterization Methods Used In This Researchmentioning
confidence: 99%
“…The SRK equation of state with parameters described above is typically sufficient to predict fluid properties. However, its results can be improved by the method of EoS regression [45] to experimental data.…”
Section: Reservoir Fluid Modelmentioning
confidence: 99%
“…All routine PVT data could be matched after marginal adjustments of the coefficients in the property correlations used to assign critical temperatures and critical pressures to the heavy end pseudo-components (Christensen, 1999). The regression algorithm applied was the Levenberg-Marquardt algorithm as proposed by Marquardt (1963).…”
Section: Eos Model Development For F1 and F2 For Use In Miscible Gas mentioning
confidence: 99%
“…Extensive routine PVT and EOR data has been measured for both oils and will be used to develop EoS models. Christensen (1999) has shown that routine PVT data can be matched by adjusting only the critical temperatures and critical pressures of the heavy end pseudo-components. However, miscibility in an oil reservoir undergoing miscible gas injection develops through a critical point and it is therefore a requirement for any EoS model to be used for simulating miscible gas injection processes that the critical point on the Swelling Test saturation point curve is matched accurately (Negahban et al, 2010).…”
Section: Introductionmentioning
confidence: 99%